Legal Protection of Traditional Knowledge Associated with Genetic Resources in Indonesia - Putranto, Muqtadir Ghani; Sulistiyono, Adi (Udayana Journal of Law and Culture; Vol 9 No 2 (2025), 2025)
The existence of ‘Traditional Knowledge associated with Genetic Resources’ in Indonesia has increased following its recent recognition under the WIPO Treaty on Intellectual Property, Genetic Resources and Associated Traditional Knowledge Adopted at Geneva on May 24, 2024. Despite this, numerous cases still occur. This study examines the critical role of Communal Intellectual Property (CIP) in Indonesia, emphasizing the urgent need to protect Traditional Knowledge (TK) and Genetic Resources (GR) amidst globalization and exploitation risks. Indonesia’s cultural diversity and rich biodiversity make CIP preservation legally and culturally imperative, yet inadequate safeguards persist. The study analyzes the legal framework on CIP through normative legal research. Findings reveal that the regulation prohibits CIP exploitation and establishes mediation mechanisms, yet enforcement challenges remain. The research underscores the government’s pivotal role in supervising CIP protection to uphold societal traditions and prevent misappropriation. By highlighting the regulation’s provisions and implementation hurdles, this study contributes to the discourse on strengthening CIP laws, urging policymakers to prioritize effective enforcement and community engagement. The analysis concludes that robust legal mechanisms are essential to safeguard Indonesia’s TK and GR as national assets, ensuring equitable benefits for indigenous communities.